Dialektika Konsep Ketuhanan dalam Ritual Lea sose pada Masyarakat Manggarai dan Gereja Katolik - Juhani, Sefrianus; Denar, Benediktus; Riyanto, FX. E. Armada (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2020)
This article aims to dialogue the concept of divinity in Manggarai, Indonesia, with the teachings of the Catholic Church. The concept of God in the Manggarai community has some similarities with the doctrine of God in the Catholic Church, that is, concerning the acknowledgment of God’s existence, involvement, and care. However, there are also matters that are quite different and that are not found in each respective context. On the one hand, the similarities can help those involved in catechesis with fresh understandings. On the other hand, the differences may enrich the outlook into knowledge about the concept of divinity, both in the context of living the Church’s teachings as well as in the context of being member of the cultural community. The results of the dialogue as explored in this article open the possibilities to help decrease the practices of syncretism on matters of faith in the Manggarai Catholic community. The approaches used by the authors to trace the concept of divinity in the two contexts are mainly qualitative with ethnographic and documentation methods. The findings are a mainstay for pastoral agents in determining certain themes for catechesis, especially those related to the concept of Godhead.